Caroticoclinoid foramen in human skulls: Incidence, morphometry and its clinical implications - Freire, Alexandre Rodrigues; Rossi, Ana Cláudia; Prado, Felippe Bevilacqua; Groppo, Francisco Carlos; Caria, Paulo Henrique Ferreira; Botacin, Paulo Roberto [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2011)
The caroticoclinoid foramen is an inconstant structure, formed by the union of the anterior and middle clinoid processes. The aim of this study was to perform an incidence and morphometry of the caroticoclinoid foramen in Brazilian human skulls and discuss its clinical implications. Eighty dry human skulls with sex distinction were used, and 3 groups of incidence were determined: General, sex, and sides. The morphometry was performed using a manual caliper and the major diameter of the foramina was measured; the values were also divided in general, according to sex and sides. The incidence of skulls with at least one foramen was 8.5%. According to the sides, 8.5% of the skulls showed foramen on the right side and 2.5% on the left. We found 2.5% of the skulls with bilateral foramen and 6.25% with unilateral foramen. In relation to sex, the foramens were found in 5% of male skulls and 12.5% of female skulls. The major diameter of this structure presented on mean, values of 5.23 mm on general, 5.18 mm on the right side and 5.35 mm on the left, 5.30 mm in male skulls and 5.18 mm in female skulls. The anatomical characteristics of this foramen should be considered in view of its clinical implications associated with neurosurgery as clinoid process removal, and symptoms as headache due to internal carotid artery alterations in this region. In conclusion knowledge of this structure supports the diagnosis and treatment of clinical complications related to this variation.
Foramen caróticoclinoideo en cráneos humanos: Incidencia, morfometría y sus implicaciones clínicas
Keywords: Carotid artery; Cranial fossa; Foramen; Middle; Morphometry